Educação sobre a morte: intervenção para o ensino superior em saúde - Carvalho, Ana Rosa Rebelo Ferreira de (2024)
Every living being has death as something inevitable in the daily life regardless of whether we are aware of it or not. Higher-level academic training in health areas aims to prepare professionals to restore the patient's health, focusing on preserving the life, often, without favoring the instrumentalization to deal with the experience of human death, triggering feelings of frustration, anxiety and impotence in these professionals. This paper adresses to develop an extesion project among healthcare academics, focused on humanized care in death situations. This is an intervention research, with a qualitative approach of exploratory type, which had as its setting a public college located in Teresina-PI, carried out with 23 students, from the courses of Psychology, Nursing, Physiotherapy and Medicine. The lead up of the intervention (extension project) consisted of: identifying students understanding of the process of death and dying; investigate the academic preparation that students receive to deal with death in the work context; elaborate and develop educational actions to train future health professionals; describe the experience of implementing an extension of death education; promote reflection of the future health professional on the theme of life and death; and evaluate the results obtained with the implementation of the extension project. The means for data collection were interviews semi-structured reports and field diaries of activities. The interviews were carried out in two distinct moments (pre and post intervention) and the extension project was carried out in 11 appointments, remotely, and use of active methodologies. The data was analyzed in light of Bardin's content analysis. The analysis of the initial interviews resulted in the categories: meanings of death; and death at graduation. The intervention was analyzed from field diary records. The analysis of the final interviews was organized into two categories: the health professional faced with death; and evaluation of the extension project. The results indicate that the meaning of death depends on several aspects such as age, culture, beliefs, social context, spiritual and religious perspectives. At studied reality, students feel helpless and unprepared to deal with death in a professional environment, making it possible to verify the need to include death education in the curriculum of health courses in order to promote discussions, experiences and practical theoretical training, as well as the development of personal and social skills, such as empathy. The death education intervention proved to be enriching when implemented with the proposal of interprofessional education, at the same time enable academics for future professional experiences, encourage self-care and search for continued training, arouse interest in the topic, as well as the indication by participants in expanding the proposal, in order to serve the entire academic community in the health field. This work was carried out with the support of CAPES - Coordination for the Improvement of Higher Education Personnel – Brazil) - Code of Financing 001, Process no. 88887.595810/2020-00